ANALYSIS OF BEEF CATTLE INVESTMENT IN SUBDISTRICT BANCAR DISTRICT TUBAN, EAST JAVA - Aulia, Hilmi; Darmansyah, Asep Darmansyah (Journal of Business and Management, 2017)
Abstract. The Study was purposed to find out the feasibility of beef cattles ystems (profit sharing system and payroll system) in District Tuban.. This research was conducted in Subdistrict Bancar, District Tuban because it is one of the subdistricts with the largest beef cattle population in Tuban. This research was conducted at Wahyu Utama farm and Plandi Rejo farm group. Wahyu Utama is a farm that uses a payroll system for farmers, while Plandi Rejo uses a profit sharing system. This study uses capital budgeting method which will be calculated NPV, IRR, and Payback Period of both kinds of system. The results of this study indicate that that in payroll system the NPV that will obtained is Rp 5,380,156,468, IRR obtained by 26.9%, Payback Period for 5 years and 7 days, and B/C Ratio is 1.207. While the company with profit sharing system will get NPV of Rp 42.677,854, IRR obtained by 12.5%, Payback Period will be achieved within 9 years 10 months, and B/C Ratio is 1.217. Based on the calculation results it can be concluded that the payroll system will be more profitable for investors.Â Keywords: Beef Cattle, NPV, IRR, Payback Period